Changes in the quality of diabetes care in Japan between 2007 and 2015: A repeated cross-sectional study using claims data. (March 2019) - Tanaka, Hirokazu; Sugiyama, Takehiro; Ihana-Sugiyama, Noriko; Ueki, Kohjiro; Kobayashi, Yasuki; Ohsugi, Mitsuru
Highlights: The changes in the quality indicators were assessed using claims data in Japan. Several quality indicators for the process of diabetes care were still suboptimal. The medication choice practices have substantially improved. Higher quality of care was observed among patients prescribed at larger hospitals. These results may provide useful benchmarks for the improvement of diabetes care. Abstract: Aim: To assess the temporal changes in the quality indicators pertaining to the process measures of diabetes care during a recent decade in Japan. Methods: A five-fold repeated cross-sectional study was conducted using health insurance claims data provided by the Japan Medical Data Center between April 2006 and March 2016. We identified 46, 631 outpatients with antidiabetic medication who regularly visited hospitals or clinics at least every three months. We evaluated the quality indicators pertaining to glycemic control monitoring, lipid profile monitoring, retinopathy screening, nephropathy screening, and appropriate medication choice. The proportions of patients who received appropriate examinations/prescriptions, by observation period and either the type of antidiabetic medication or facility type were estimated using generalized estimating equation (GEE) models with multiple covariate adjustments. Results: The quality indicator values for appropriate medication choice and nephropathy screening improved between 2007 and 2015, whereas those for glycemic control monitoring and retinopathy screening remained suboptimal. Patients prescribed medications in larger hospitals were likelier to undergo the recommended examinations (e.g. retinopathy screening: 36.1% (95% CI: 35.4–36.7%) for clinic, 40.6% (95% CI: 39.1–42.2%) for smaller hospital, and 46.0% (95% CI: 44.8–47.2%) for larger hospital in 2015). Conclusions: Several process measures of diabetes care remained suboptimal in Japan.